Strategies for Computer Science Education in University - Leonard, Shaibu; Haruna, Mohammed Sani; Obetta, Idoko Eberechukwu Joy; Chinenye, Udemba Esther (Center of Research and Innovation Strengthen LP2M UNM, 2024)
The study investigated the Strategies for Computer Science Education Programme at Kogi State University, Anyigba. The purpose of the study was specifically targeting the types of computer facilities, their importance in computer education, factors militating against effective use for teaching and learning and strategies to be adopted for effective teaching and learning. Four research questions and four hypotheses guided the study. A descriptive survey design was adopted for the study. 100 computer students were purposively sampled for the study. Computer Education Checklist (CEC) and Strategies for Computer Education Questionnaire (SCEQ) were used as data collection tools. Percentage, mean and standard deviation were used to analyze the data collected. Analysis revealed that (1) the types of computer facilities available for computer education are laptops, printers, computer laboratories, desktops, monitors, CPU and Diskettes, CDs and flash (2) the benefits of computer education are that computer education programme enhances efficiency in teaching and learning, makes instruction in the class to be lively, and enhances individualization of learning among others, (3) several factors militate against computer education programmes in the study area are lack of skills, cost of the facilities, weak infrastructure, lack of relevant software, limited access to the internet and others and (5) strategies to handle the challenges above are that computer training for teachers, procurement of hardware facilities, curriculum development, and software development, maintenance of computer systems, adequate funding, and increase in government allocation to computer studies and provision of internet facilities should be used.